Sosialisasi Pemanfaatan Jerami Jagung Sebagai Pakan Ternak Di Desa Anggoli Kecamatan Sibabangun Kabupaten Tapanuli Tengah - Ulfa Nikmatia; Zakiyah Nasution; Doharni Pane; Angelia Utari Harahap; Nursanti Laia (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2026)
Silage is a type of forage preserved by storing it in a silo under anaerobic conditions. Lecturers from the Animal Husbandry Study Program, Faculty of Agriculture, Graha Nusantara University, Padangsidimpuan, conducted community service in Anggoli Village, Sibabangun District, Central Tapanuli Regency in October 2025. This activity aimed to utilize agricultural waste, particularly corn straw, to meet the feed needs of ruminant livestock such as cattle and goats. Furthermore, this activity also trained the community to utilize existing potential optimally, enabling optimal utilization of corn straw waste. Utilizing corn straw waste can reduce waste disposal by increasing agricultural production. The tools used included a shredder, clear plastic, plastic drums, and tarpaulin. The results of this community service included improving farmer skills by making corn straw silage, which can be used as animal feed with high nutritional value. Keywords: Corn Straw, Silage, Feed